FLORISTIC AND SUCCESSIONAL CHARACTERIZATION AS A SUPPORT FOR CONSERVATION AND MANAGEMENT OF PNMCBio, SOROCABA/SP - Coelho, Samuel; Cardoso-Leite, Eliana; Devides Castello, Ana Carolina [UNESP] (Centro Pesquisas Florestais, Ufsm, 2016)
The study was conducted at the Natural Municipal Park Corredores da Biodiversidade (PNMCBio) in Sorocaba-SP, with the aim to evaluate the floristic composition of the tree component and the successional stage of a forest with about 31 hectares. Thereunto, were allocated 64 plots of 10 x 10 meters randomly distributed in the area. All individuals with CBH (circumference at the breast height) equal to or greater than 15 cm were included. We estimatedthe diversity through the Shannon diversity index (H') and evenness through the Pielou index (J'). The species were characterized in successional groups, dispersal syndromes, categories of threat, distributional range and indicator of the regeneration stage. We sampled 1088 individuals distributed into 79 species, 54 genera and 29 families. The H' was estimated in 3,421 and the J' in 0.78, values close to those found in other areas of similar vegetation formations. We sampled four endangered species, 11 Atlantic Forest endemic species and two species restricted to Seasonal Semideciduous Forest in the Atlantic Forest domain. The fragment is in an intermediate stage of succession, being of paramount importance to conservation and management for the maintenance of local and regional biodiversity.
Keywords: seasonal semideciduous forest; successional stage; management